Grób podwójny z cmentarzyska Piaski, gm. Kleszczów, woj. piotrkowskie, a niektóre zagadnienia obrządku pogrzebowego kultury przeworskiej - Olędzki, Marek (Acta Universitatis Lodziensis. Folia Archaeologica, 1984)
The article contains a presentation of the burial from Przeworsk-culture cemetery of Piaski near Bełchatów, which is interesting due to its form. The burial in question was richly equipped with objects, which for their most part can be easily dated (Tabl. III, IV, V, VI). They were submitted to careful typological and chronological analysis the result of which was presented in Table I. The burial equipment was fully of the so called male-sex indicator character while the analysis of bone material would rather point that a woman and a man were buried in it. Such a situation is know from other Przeworsk-culture cemeteries in which similar burials containing fragments of both men and women were discovered. Many scholars would account for it as a form of offering from the life of widows for their diseased husbands. In turn, burials containings remains of adults and children were supposed to testify to offerings of children for their parents. The author, analyzing extensive data sources provided by burials from Przeworsk-culture cemeteries analyzed anthropologically (Tab. II), tries to prove that genesis of collective burials including double burials as the discussed grave at Piaski should not be sought in human offerings. An argument in this case may be among others, the type of eqipment having characteristics of the archeological sex indicator. Oftentime in burials with remains of women and men the equipment in its character points exclusively that a woman was buried there. That is also confirmed by the burial from. It was also discovered that in graves of adults and children the equipment is not connected with an adult at all. These and other arguments, such as e.g. differentiated combination of sexes and age of persons buried in collective graves (Tabl. III) make it necessary to seek for other causes than human offerings which led to development of collective burials.